南極氷床の表面質量収支と堆積環境 - 本山, 秀明; Motoyama, Hideaki (2016)
南極氷床における20年間の雪尺観測から見えてきた氷床表面質量収支の年々変動についてまとめた。2000-2002を境に減少傾向から増加傾向となった。さらに地形に支配される堆積環境について解析した。時間があれば、他のトピックスも紹介する。 We study the spatial and temporal variability of yearly surface mass balance on Antarctic ice sheet for the past 20 years. Pattern of snow deposition is generally decided by surface topography. Polar Meteorology and Glaciology Group seminar / 気水圏コロキウム 日時：6月29日（水）10:00-10:50 場所：C301（3階セミナー室） conference object